Quantitative analysis of oxyresveratrol content in artocarpus lakoocha and 'Puag-Haad' - Suthira Maneechai (2018)
Objective: To develop a thin-layer chromatography (TLC) densitometric method for the determination of oxyresveratrol content in Artocarpuslakoocha heartwood and in the traditional drug 'Puag-Haad'. Materials and Methods: Sample solution of A. lakoocha heartwood was prepared by Soxhlet extraction of the plant material in ethanol, whereas the Puag-Haad solution was obtained by dissolving the drug in methanol. Analysis of each sample solution was performed on a Silica gel 60 F 254 TLC plate (20 × 10 cm) with methylene chloride/methanol (85:15) as the mobile phase. After development, the TLC plate was examined with a TLC scanner in the absorbance mode at 254 nm. The newly developed analytical method was validated using an authentic sample of oxyresveratrol previously isolated from A. lakoocha heartwood, and was used to analyze the oxyresveratrol content in samples of A. lakoocha heartwood and the traditional drug Puag-Haad. Results: A sensitive and reliable TLC densitometric method was successfully developed. The method was validated in terms of accuracy (99.11-102.60%) and precision (1.66-4.23% coefficient of variation). The limits of detection and quantitation were 15.6 and 52 ng/spot, respectively. The amounts of oxyresveratrol in 3 samples of A. lakoocha heartwood collected from its natural habitat were 49.0-182.3 mg/g, whereas those in 11 commercial samples were in the range of 23.4-69.6 mg/g. The oxyresveratrol contents in 2 samples of traditional drug Puag-Haad were 780.1 and 837.5 mg/g. Conclusion: The TLC densitometric method developed in this study is a simple, convenient, sensitive and reliable procedure. It was an effective analytical tool for the evaluation of oxyresveratrol content in both A. lakoocha heartwood and the traditional drug Puag-Haad. Copyright © 2009 S. Karger AG, Basel.